Certainty of Fulfilling the Subjective Requirements of an Agreement in the Case of PPJB; Analysis of Decision Number 697/PDT.G/2021/PN.TNG - Husen, Nur Afni; Adhari, Ade (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the fulfillment of subjective conditions in an agreement, such as the competence of the parties and free will, serves as the basis for the legal validity of the agreement. However, in reality, as seen in Case Decision Number 697/PDT.G/2021/PN.TNG, non-formal factors such as unequal bargaining positions and emotional pressures also influence the annulment of the Sale and Purchase Agreement (PPJB). This study aims to analyze the legal certainty of fulfilling the subjective conditions of agreements and the judge's considerations in this case. A normative juridical approach was employed, analyzing the court's decision and contract law theory. The research findings indicate that while subjective conditions were formally met, the judge annulled the PPJB by considering substantive justice. Unequal bargaining positions and psychological pressures were the main reasons for the annulment. This study emphasizes that the protection of individual rights and balanced justice is the primary principle in contract annulments, surpassing the mere fulfillment of formal conditions.